2011
DOI: 10.1016/j.pbb.2011.07.001
|View full text |Cite
|
Sign up to set email alerts
|

The smoking cessation drug varenicline improves deficient P20–N40 inhibition in DBA/2 mice

Abstract: Varenicline, an FDA approved smoking cessation pharmacotherapy, is an α4β2* nicotinic acetylcholine receptor (nAChR) partial agonist and an α7* nAChR full agonist. Both subtypes of nAChR are involved in modulating auditory evoked responses in rodents. In DBA/2 mice, an inbred strain, auditory evoked responses to paired auditory stimuli fail to inhibit to the second stimulus. This mouse strain replicates the auditory evoked response inhibition deficit experienced by the majority of schizophrenia patients. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 66 publications
(100 reference statements)
1
5
0
Order By: Relevance
“…Consistent results obtained in different animal species ranging from rodent to nonhuman primates further strengthened the role of a7 nAChRs in cholinergic system functioning. Preclinical studies have demonstrated the efficacy of several a7 nAChR agonists in an N40 sensory gating model (Hashimoto et al, 2005;Simosky et al, 2008;Wildeboer-Andrud and Stevens, 2011), in particular ABT-107 (Radek et al, 2012). Other molecules such as TC-5619, SSR-180711, A-582941, or encenicline also demonstrated efficacy in cognitive models (Pichat et al, 2007;Tietje et al, 2008;Mazurov et al, 2012;Prickaerts et al, 2012).…”
Section: B Schizophreniamentioning
confidence: 99%
“…Consistent results obtained in different animal species ranging from rodent to nonhuman primates further strengthened the role of a7 nAChRs in cholinergic system functioning. Preclinical studies have demonstrated the efficacy of several a7 nAChR agonists in an N40 sensory gating model (Hashimoto et al, 2005;Simosky et al, 2008;Wildeboer-Andrud and Stevens, 2011), in particular ABT-107 (Radek et al, 2012). Other molecules such as TC-5619, SSR-180711, A-582941, or encenicline also demonstrated efficacy in cognitive models (Pichat et al, 2007;Tietje et al, 2008;Mazurov et al, 2012;Prickaerts et al, 2012).…”
Section: B Schizophreniamentioning
confidence: 99%
“…In DBA/2 mice, the drug improves gating by decreasing S2 amplitude at low doses and increasing S1 amplitude at higher doses. 50 The dose dependence of varenicline may be due to the observation that α7 receptors desensitize as a function of increasing agonist concentration, 97 reducing S2-mediated effects at high doses of drug. A pilot human study using a ‘low' dose (0.012 mg kg −1 ), however, showed no significant effects of acute varenicline administration on gating.…”
Section: Hippocampal Gating As a Translational Tool: A Review And Evamentioning
confidence: 99%
“…Accordingly, the gating of the P20/N40 in various mouse strains correlated with their hippocampal α7 nAChR expression [63]. After administration of nicotine or other α7 nAChR agonists the P20/N40 gating of each strain was improved [6366], providing converging support for the α7 nAChR as a viable therapeutic target in schizophrenia [43, 67, 68]. …”
Section: Genetic and Pathophysiological Linkage Between The α7 Nacmentioning
confidence: 99%